Perspectives internes des entreprises minières en lien avec les obligations de consultation des peuples autochtones : un enjeu de gouvernance - Boirin, Zoé (Université Paris 1 ; Université d'Ottawa, 2025)
Le cadre politico-juridique canadien qui régit la consultation des peuples autochtones engendre une situation de « régulation négociée » entre les entreprises minières et ces peuples. Autrement dit, les pratiques de consultation sont élaborées à travers un processus de négociation entre les entreprises et les communautés autochtones. En raison, notamment, de l'encadrement juridique des activités minières, encore fondé sur le principe du free entry, les entreprises minières occupent une place prépondérante dans la manière dont les perspectives et les intérêts des peuples autochtones sont intégrés dans le développement minier. Le principal enjeu de cette régulation négociée réside dans l’asymétrie des rapports de force entre les différents acteurs, souvent défavorable aux peuples autochtones. Dans ce contexte, cette thèse s'inscrit dans le constat qu'il existe peu de recherches sur les pratiques internes des entreprises minières en matière de consultation des peuples autochtones. Adoptant une approche sociojuridique, nous avons mené une recherche empirique fondée sur deux études de cas : la première auprès d’une entreprise opérant à l’échelle provinciale/territoriale, et la seconde au sein de la filiale d’une multinationale. Les résultats issus de ces études de cas nous ont permis d’identifier des points de convergence et de divergence entre les deux entreprises, confirmant ainsi la diversité des acteurs au sein de l’industrie et des influences qui les façonnent. Ces résultats nourrissent également la réflexion sur la régulation des pratiques de consultation, notamment en ce qui concerne l’enjeu de l’asymétrie des rapports de force. The Canadian politico-legal framework governing the consultation of Indigenous peoples creates a situation of "negotiated regulation" between mining companies and these peoples. In other words, consultation practices are developed through a negotiation process between companies and Indigenous communities. This situation is largely influenced by the legal framework surrounding mining activities, which still relies on the principle of free entry, giving mining companies a dominant role in determining how the perspectives and interests of Indigenous peoples are integrated into mining development. The primary issue of this negotiated regulation lies in the asymmetry of power dynamics between the various actors, often to the detriment of Indigenous peoples. In this context, this thesis arises from the observation that there is limited research on how mining companies internally develop their consultation practices with Indigenous peoples. Adopting a socio-legal approach, we conducted empirical research based on two case studies: the first with a company operating at the provincial/territorial level, and the second within the subsidiary of a multinational corporation. The findings from these case studies allowed us to identify points of convergence and divergence between the two companies, thus confirming the diversity of actors within the industry and the various influences shaping them. These results also contribute to the
Issue: 2025PA01D025
Keywords: Consultation; Corporations; Entreprises; Indigenous peoples; Mining projects; Peuples autochtones; Projets miniers; Sociologie du droit; Sociology of law

L’action en réparation des préjudices subis en cas d’atteinte du droit à un environnement sain par l’exploitation minière : cas des communautés locales vivant dans la zone CEMAC - Andosmoui, Nature de Destin (Université de Montréal, 2023)
La zone CEMAC (Communauté Économique et Monétaire de l’Afrique Centrale) dispose d’innombrables ressources minières solides et liquides. Dans cette zone, l’exploitation minière est considérée comme un véritable levier stratégique de développement socio-économique. C’est pour cette raison que la vision 2025 ainsi que le Programme Économique Régional de cette zone communautaire l’ont érigé comme pilier de l’émergence économique et initié, entre autres, la création d’une académie minière, les projets transfrontaliers d’exploitation minière ainsi que l’adoption d’un code minier communautaire. Au-delà des commodités économiques qu’apportent l’exploitation minière aux pays membres de la CEMAC, il sied de souligner que cette activité demeure concurremment une des principales sources de dégradations environnementales dans cette sous-région. En effet, l’exploitation minière se déroule en plusieurs phases. Pendant la phase dite de concassage ou de broyage, des contaminants tels que le cadmium, le plomb, le sélénium et l’arsenic, utilisés pour extraire les minerais, sont rejetés dans l’air. Au contact de celui-ci, ces contaminants subissent des transformations physico-chimiques et finissent par polluer l’air. Lors de la phase dite de lessivage, certains de ces constituants toxiques composés généralement d’azote, de cyanure, d’ammoniac, de nitrate ou de nitrite sont, quant à eux, déversés dans des eaux domestiques utilisées par les communautés locales. Ces substances chimiques ne se dissolvent pas dans ces eaux. Au contraire, elles y restent pendant plusieurs années et finissent par devenir des foyers de pollution des eaux domestiques. Aujourd’hui, ces répercussions environnementales, qui constituent indéniablement une violation du droit à un environnement sain (DES), menacent non seulement la santé mais également la survie de plusieurs communautés locales vivant dans les pays de la zone CEMAC. Compte tenu des préjudices qu’elles subissent, ces dernières sont légitimement en droit de demander réparation. Selon certaines recherches dont celles effectuées par le Centre de ressources sur les entreprises et les droits de l’homme, malgré la multiplication des atteintes du DES du fait de l’exploitation minière et les dénonciations de la société civile dans cette sous-région d’Afrique, les principales victimes, en l’occurrence les communautés locales, n’entreprennent que rarement voire quasiment jamais une action en réparation devant les juridictions compétentes. C’est fort de ce constat qu’à travers une analyse positiviste de certains éléments règlementaires et socio-contextuels, cette thèse s’est proposée dans un premier temps d’identifier les principaux obstacles à l’origine de cette quasi-absence d’actions en réparation des communautés locales. Dans un second temps, elle s’est astreinte à proposer deux grandes pistes de réforme en la matière. Un double objectif sous-tend cette proposition. Elle vise d’abord à ménager le mécanisme d’action en réparation en la matière afin de faciliter voire encourager les communautés locales victimes des violations de leur droit à un environnement sain par l’exploitation minière à saisir les juridictions compétentes. Ensuite, elle vise également à garantir une obtention effective de l’indemnisation des préjudices qu’elles subissent du fait de l’activité minière. The CEMAC zone (Economic and Monetary Community of Central Africa) has countless solid and liquid mining resources. In this zone, mining is considered a real strategic lever for socio-economic development. This is why the 2025 vision and the Regional Economic Program of this community zone have established it as a pillar of economic emergence and initiated, among other things, the creation of a mining academy, cross-border mining projects and the adoption of a community mining code. In addition to the economic benefits that mining brings to CEMAC member countries, it should be noted that this activity remains one of the main sources of environmental degradation in this sub-region. Indeed, mining takes place in several phases. During the crushing or grinding phase, contaminants such as cadmium, lead, selenium and arsenic, used to extract the ores, are released into the air. In contact with the air, these contaminants undergo physical and chemical transformations and end up polluting the air. During the leaching phase, some of these toxic constituents, generally composed of nitrogen, cyanide, ammonia, nitrate or nitrite, are discharged into domestic water used by local communities. These chemicals do not dissolve in these waters. On the contrary, they remain there for several years and end up becoming sources of domestic water pollution. Today, these environmental repercussions, which undeniably constitute a violation of the right to a healthy environment (DES), threaten not only the health but also the survival of several local communities living in the countries of the CEMAC zone. Given the damage they suffer, these communities are legitimately entitled to claim compensation. According to some research, including that carried out by the Resource Center on Business and Human Rights, despite the multiplication of DES violations due to mining and the denunciations of civil society in this sub-region of Africa, the main victims, in this case the local communities, rarely, if ever, take action for compensation before the competent jurisdictions. It is with this in mind that, through a positivist, comparative and interpretative analysis of certain well-known regulatory and socio-contextual elements, this thesis first proposes to identify the main obstacles at the origin of this near absence of reparation actions by local communities. Secondly, it has attempted to propose two major avenues of reform in this area. The aspiration of this singular proposal is twofold. Firstly, it aims to spare the mechanism of reparation action in this matter in order to facilitate and even encourage local communities who are victims of violations of their right to a healthy environment by mining operations to bring their case before the competent jurisdictions. Secondly, it also aims to guarantee that the damages suffered by these communities as a result of the mining activity are effectively compensated.
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/28576/Andosmoui_Nature_de_Destin_2022_these.pdf
Keywords: Civil liability; Class action; Compensation fund; Droits de la personne; Environment; Environmental damage; Exploitation minière; Fonds d’indemnisation; Human rights; Mining; Préjudices environnementaux; Recours collectif; Responsabilité civile

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Permalink: https://repository.canterbury.ac.uk/item/95yw5/environmental-protection-under-national-legislation-and-agreements-between-oil-and-gas-multinational-corporations-and-host-communities
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

Le régime juridique de l'activité pétrolière offshore en Afrique Subsaharienne, le cas d'un état francophone du Golfe de Guinée : la Côte d'Ivoire - Danhoue Gogoue, Achille (Université de Limoges, 2021)
Les États du golfe de Guinée en général et la Côte d’Ivoire en particulier ont une façade maritime sur l’Océan Atlantique Sud et possèdent un bassin sédimentaire riche en hydrocarbures. L’exploitation de cette ressource naturelle permet à ces États d’engranger des capitaux pour financer leur développement, mais elle est au cœur d’enjeux économiques, stratégiques, géopolitiques et environnementaux qui ont suscité la mise en place d’un cadre juridique qui mérite d’être connu. Ce cadre juridique qui inclut les normes internationales et les normes nationales s’applique à l’amont de l’activité pétrolière offshore ainsi qu’aux conséquences qu’elle est susceptible d’engendrer sur l’environnement marin et côtier.Ainsi, le régime juridique applicable à l’activité pétrolière offshore vise deux objectifs : l’encadrement des opérations pétrolières d’une part avec les rapports interpersonnels et interétatiques qu’elles induisent et l’encadrement des conséquences de cette activité en vue d’une protection efficace de l’environnement.
Keywords: Activité pétrolière; Côte d'Ivoire; Droit; Economic issues; Enjeux économiques; Environnement; Guinée; Golfe de; Hydrocarbon; Hydrocarbure; Oil activity

Protection de l'intérêt général et investissements directs étrangers dans le secteur minier malien: contribution aux réformes du droit OHADA - Kanta, Korotoumou (Université de Montréal, 2020)
Dans la présente étude, la protection des droits de l’homme et la promotion du développement durable sont considérées comme des préoccupations d’intérêt général. Partant de l’hypothèse d’une surprotection par le droit international de l’investissement de l’investisseur étranger, l’auteur tente de démontrer que le rééquilibrage des droits et des obligations entre investisseurs étrangers et États hôtes de l’investissement, amorcé dans les pays développés n’est pas perceptible dans les pays du sud. En effet, l’analyse faite des politiques et cadres juridiques relatifs aux investissements étrangers des pays de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) semble conforter la thèse selon laquelle les mécanismes de prise en compte des préoccupations d’intérêt général sont relativement inadéquats, ou à tout le moins, insuffisamment efficaces. Les politiques de promotion et de protection de l’investissement direct étranger (IDE) y sont privilégiées, laissant peu ou pas de place aux politiques de protection axées sur les enjeux d’intérêt général. Il en résulte donc un déséquilibre marqué entre les mécanismes de promotion mis en œuvre dans ces pays et la nécessaire prise en compte des préoccupations liées au développement durable et à la protection des droits de l’homme. En nous appuyant sur le cas des investissements miniers au Mali, la présente étude permet de mettre en lumière ce déséquilibre tout en insistant sur les faiblesses systémiques et les conditions asymétriques dans lesquelles les instruments de régulation des investissements miniers sont produit et mis en œuvre. Les pistes de réflexion suggérées privilégient des approches fondées sur la convergence, à l’échelle des pays membres de l’OHADA, des mécanismes de production et de mise en œuvre des instruments juridiques entourant les investissements étrangers. Dans cette nouvelle configuration, le pouvoir d’uniformisation et d’harmonisation de l’OHADA est fortement sollicité. The protection of both human rights and sustainable development are viewed as real concerns of general interest in this thesis. These constitute a real challenge in international law of investments that often overprotects the foreign investor. The need to consider the general interest has been manifested in some case law before gaining the traditional way. This positive trend, consisting in including concerns of general interest remains exceptional, particularly in the investment policies and legislation in developing countries. On one hand, the legal regime of foreign direct investment (FDI) shows some disproportions of negotiating power to sign bilateral investment treaties negotiated with developed countries. On the other hand, government contracts present the same failures. Furthermore, FDI promotion and protection policies have become priorities on issues of general interest. The imbalance of the legal regime of FDI is reflected in the national investment laws in developing countries. Mining in Mali is a perfect example of the challenge of protecting the public interest in the legal framework of FDI. Avenues to find the way out have therefore been suggested in the context of the Organization for the Harmonization of Business Law in Africa (OHADA). The main goal is to promote a better protection of the general interest in Mali as well as in its other State members. These lines of thought have favored standardization of FDI in OHADA's body of law by focusing on the admission phase and the negotiation of investment treaties on behalf of the State members.
Keywords: FDI; Foreign direct investment; General interest; Intérêt général; Investissements; Investissements directs étrangers; Investments; Mines; OHADA; Responsabilité Sociétale de l'Entreprise; Social responsibilities of corporations responsibility